2001
DOI: 10.1021/jf001175v
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Phytosterol Oxides and Cholesterol Oxides in Cultured Macrophage-Derived Cell Lines

Abstract: The cytotoxicity of cholesterol and a mixture of beta-sitosterol/campesterol (50%/40%) and their oxides was examined in a cultured-derived macrophage cell line, C57BL/6. Cell numbers, lactate dehydrogenase (LDH) leakage, protein content, lipid uptake, and mitochondria dehydrogenase activity were determined after exposure of cell mononlayers to sterols and sterol oxides at a concentration of 200 microg/mL for up to 120 h. Results indicate that the oxides of cholesterol, beta-sitosterol, and campesterol exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 29 publications
3
68
1
1
Order By: Relevance
“…All compounds exhibited similar cytotoxicity as indicated by LDH leakage, cell viability and mitochondria dehydrogenase activity, although oxyphytosterols exerted less severe effects than cholesterol oxides. 23 In the presence of the pancaspase inhibitor, Z-VAD.fmk, apoptotic events were not completely suppressed. 31 Hence, 7b-OHsito may trigger apoptosis through postmitochondrial caspase cascades and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All compounds exhibited similar cytotoxicity as indicated by LDH leakage, cell viability and mitochondria dehydrogenase activity, although oxyphytosterols exerted less severe effects than cholesterol oxides. 23 In the presence of the pancaspase inhibitor, Z-VAD.fmk, apoptotic events were not completely suppressed. 31 Hence, 7b-OHsito may trigger apoptosis through postmitochondrial caspase cascades and DNA fragmentation.…”
Section: Discussionmentioning
confidence: 98%
“…However, only a few data are available on biological activities of oxyphytosterols. 21,22 It was reported that they cause cellular damage in cultured macrophage-derived cell lines 23 and that hydroxysitosterol induces apoptosis of U937 cells, accompanied by a reduction of cellular glutathione. 24 Furthermore, numerous studies reported atherogenic 25,26 and cytotoxic properties [27][28][29][30] of cholesterol oxides, leading to apoptosis or necrosis in various cell types.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few reports regarding the cytotoxic effects of POPs, which seem to be less severe [23][24][25]. Some research works attending to find out a proper methodology for the identification and quantification of POPs in vegetable oils, potato chips and French fries [26][27][28], milks [29], enriched spreads [30,31] have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years the cytotoxic effect of phytosterol oxidation products (POP) was investigated and published studies show the toxic activity of POP and cholesterol oxidation products (COP). Some studies present similar effects for both, while others suggest POP have a stronger effect than COP (Adcox et al, 2001;Vejux et al, 2012). Several studies pointed to the potential chemotherapeutic effects of particular phytosterol oxides, because of selective apoptosis induction in cancer cell lines (Samali et al, 1996).…”
Section: Introductionmentioning
confidence: 96%